The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pone.0278169
|View full text |Cite
|
Sign up to set email alerts
|

Both trust in, and polarization of trust in, relevant sciences have increased through the COVID-19 pandemic

Abstract: While attempts to promote acceptance of well-evidenced science have historically focused on increasing scientific knowledge, it is now thought that for acceptance of science, trust in, rather than simply knowledge of, science is foundational. Here we employ the COVID-19 pandemic as a natural experiment on trust modulation as it has enabled unprecedented exposure of science. We ask whether trust in science has on the average altered, whether trust has changed the same way for all and, if people have responded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The social media discussion of COVID-19 has made the question of whether what is disseminated is verified scientific information or misinformation/fake news increasingly critical. Radrizzani et al (2023) surveyed a sample of the United Kingdom public about how their trust in science had been affected by the introduction of the first COVID-19 vaccines. They found that it was much more common for people to report that not only their trust had increased than that it had decreased but also that trust decreased among those who had little trust in science to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…The social media discussion of COVID-19 has made the question of whether what is disseminated is verified scientific information or misinformation/fake news increasingly critical. Radrizzani et al (2023) surveyed a sample of the United Kingdom public about how their trust in science had been affected by the introduction of the first COVID-19 vaccines. They found that it was much more common for people to report that not only their trust had increased than that it had decreased but also that trust decreased among those who had little trust in science to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…But equally, during the pandemic, many on the populist right (including groupings like "UsforThem") claimed that COVID measures represented the capture of policy by the "scientific establishment" against the interests of "the people" (Kingsley, 2023). Indeed, as the pandemic went on, views about science in the UK became increasingly politically polarized-although, absolute levels of support for science and scientists increased (Radrizzani et al, 2023).…”
Section: The Current Study In Contextmentioning
confidence: 99%
“…UK academics are generally trusted by the public [62]. The pandemic might easily have dented this trust [63] but luckily, the British Academy's recent study found that academics are still widely trusted [64]. Cybersecurity academics work with psychologists and computer scientists to understand how to deliver cybersecurity guidance to the public.…”
Section: Cybersecurity Academics As Sourcementioning
confidence: 99%